New Paraquat Requirements - Frederick M. Fishel (EDIS)
EPA is requiring registrants of paraquat products to revise their labels. The revisions are to mitigate potential exposure to paraquat, an acutely toxic herbicide used in non-selective weed control. Labels will also contain a statement regarding the training requirements that will be mandatory for certified applicators of paraquat. This document will present an overview of the new label revisions.